MECHANISMS OF COMMUNITY CONTROL AMONG STUDENTS (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article analyzes the content, essence, and practical significance of community control mechanisms among students within Uzbekistan's higher education system. Based on both scientific and international experiences, the role of students in educational processes, governance, evaluation, and monitoring is highlighted. The paper presents concrete scientific conclusions and practical recommendations concerning the forms, implementation mechanisms, and paths for improving public oversight. Research findings demonstrate that community participation among students contributes to enhancing their social activity, leadership capacities, and the overall effectiveness of educational processes.